Report of the Secretary-General : on the work of the organization - United Nations Economic and Social Council, New York, NY.; United Nations Economic and Social Council, New York, NY. (United Nations: New york, 1976)
This report was prepared as a study of the situation of developing countries with regard to: (1) The results already obtained and the needs and prospects for the use of electronic computers in accelerating the process of economic and social development; (2) The various forms which international action may take to intensify co-operation in the field of computers and (3) The role which the United Nations can play in promoting international co-operation in that field, with emphasis on questions concerning the transfer of technology, the training of personnel and technical equipment. Part I deals with programs for developing the use of computer technology to facilitate the economic growth of developing countries and Part II presents some of the caveats, barriers and incentives that must be considered in the application of this technology. Recommendations of the study are: education and training of computer technology to accelerate economic and social development must receive first priority, each developing nation needs a broad national policy, and international cooperation must be increased. Nine appendices present background for the study. [Not available in hard copy due to marginal legibility of original document.] (AB)
Availability: United Nations Economic and Social Council, New York, New York.
ERIC Note: Report prepared for the Forty-ninth session, Agenda item 15.
Microfiche.
Keywords: Computers; Developing Nations; Economic Development; Personnel; Social Development; Technology; Training; United Nations Economic and Social Council